Development and validation of a Guinea pig model for concurrent allergic rhinitis and asthma using recombinant Der f 2 - Feng Xu; Li Hu; Jianzhong Wang; Lineng Zhang (BMC Pulmonary Medicine)
Abstract Background This study aimed to develop a guinea pig model of concurrent allergic rhinitis and asthma. Methods Thirty-three guinea pigs were randomly divided into the control group and the experimental group. Guinea pigs in the experimental group were sensitized by intraperitoneal injection of recombinant wild-type Dermatophagoides farinae group 2 allergen (wt Der f 2) plus Al(OH)3 on day 1 and 8, followed by inhalation of an aerosol of wt Der f 2 on day 16 and 23. The sensitized guinea pigs were challenged with intranasal instillation of wt Der f 2 plus Al(OH)3 gel on day 19 and 26 for nasal symptoms scoring, and on day 30 for the active cutaneous anaphylaxis (ACA) test. Control group guinea pigs received normal saline (N.S.) plus Al(OH)3 in parallel. Cutaneous provocation tests were performed to exclude nonsensitized guinea pigs, and nasal symptom assessments were conducted to exclude non-allergic guinea pigs from the study. The allergic airway model was finally validated using the ACA test, Evans blue dye quantification with wt Der f2, histopathology evaluation, and immunohistochemistry analysis of MUC5AC expression in both nasal mucosa and lung tissue. Results Two guinea pigs with negative cutaneous reactions and three with less than 5 points of the nasal symptom assessment were excluded from the experimental group. The ACA test showed enhanced allergic reactions in the experimental group, and the quantification of extravasated Evans blue dye demonstrated significantly higher absorbance in the wt Der f 2 spots compared to mu Der f 2. Histologic analyses illustrated pathologic features typical of allergic rhinitis and asthma. MUC5AC levels in the nasal mucosa and lung samples were significantly higher in the experimental group than in the control group. Conclusion We successfully established a guinea pig model of concurrent allergic rhinitis and asthma using a combination of sensitization, challenge, and validation methodologies with the allergen Der f 2, suitable for pathophysiological studies. Clinical trial number Not applicable.